POST TREATMENT OF POULTRY SLAUGHTERHOUSE WASTEWATER AND APPRAISAL OF THE ECONOMIC OUTCOME - Yetilmezsoy, Kaan; Turkdogan-Aydinol, Ilter; Gunay, Aylin; Ozis, Idil (GH ASACHI TECHNICAL UNIV IASI, 2011)
Recovery of residual ammonium nitrogen (NH4+-N) from dissolved air flotation (DAF) pretreated poultry slaughterhouse wastewater was studied by means of magnesium ammonium phosphate hexahydrate (MgNH4PO4.6H2O, MAP) precipitation in a lab-scale batch study. The maximum recovery values were obtained as 80.2%, 97.1% and 53.6% with the addition of MgCl2.6H2O + KH2PO4, NaH2PO4.2H2O + MgSO4.7H2O, and MgOHCO3 + 85% H3PO4 at pH 9.5, respectively. Based on the physicochemical findings, subsequent batch experiments were conducted at pH 9.5 for eight different molar ratios (Mg2+: NH4+-N:PO43--P) applied as overdose (1.2: 1: 1, 1.5: 1: 1, 1: 1: 1.2, 1: 1: 1.5) and underdose (0.5: 1: 1, 0.8: 1: 1, 1: 1: 0.5, 1: 1: 0.8). Results indicated that the stoichiometric ratio (Mg2+: NH4+-N:PO43--P = 1: 1: 1) was found to be sufficient to obtain high recovery values. A detailed economic analysis of the present process demonstrated that the cost of NH4+-N recovery was estimated as 0.297(sic)/m(3) or 1.753 (sic)/kg NH4+-N-removed for the proposed application. The rate of reaction was found to be very fast, being completed within minutes, and cost effective in large-scale poultry slaughterhouse facilities.
Keywords: ammonium nitrogen; dissolved air flotation; magnesium ammonium phosphate; poultry slaughterhouse wastewater; LANDFILL LEACHATE; AMMONIUM REMOVAL; RECOVERY; STRUVITE; PHOSPHORUS; MAGNESIUM; ELECTROCOAGULATION; CRYSTALLIZATION; PHOSPHATE; COD; Environmental Sciences & Ecology